Sarcopenia and physical independence in older adults: the independent and synergic role of muscle mass and muscle function. Issue 2 (8th November 2016) - dos Santos, Leandro; Cyrino, Edilson S.; Antunes, Melissa; Santos, Diana A.; Sardinha, Luís B.
Abstract: Background: The loss of skeletal muscle mass (MM) or muscle function (MF) alone increases the risk for losing physical independence in older adults. We aimed to examine the independent and synergic associations of low MM and low MF, both criteria of sarcopenia, with the risk for losing projected physical independence in later life (+90 years old). Methods: Cross‐sectional analyses were conducted in 3493 non‐institutionalized older adults (1166 males). Physical independence was assessed with a 12‐item composite physical function scale. Logistic regression was used to estimate the odds‐ratio (OR) for being at risk for losing physical independence. Results: Approximately 30% of the participants were at risk for losing physical independence at 90 years of age. Independent analysis demonstrated that participants with low MM had 1.65 (95%CI: 1.27–2.31) increased odds for being at risk for losing physical independence and participants with low MF had 6.19 (95%CI 5.08–7.53) increased odds for being at risk. Jointly, having a low MM and a low MF increased the risk for losing physical independence to 12.28 (95%CI 7.95 to 18.96). Conclusions: Although low MM represents a risk factor for losing physical independence, low MF seems to play a more dominant role in this relationship, with the presence of both sarcopenia criteria representing a substantial risk for losing physical independence in later life.